Improving petroleum liquid flow in a rotating disk apparatus using structured inner surfaces and polymeric additives - Rashed, Musaab Kadem (2017)
The most economically feasible technique to transport petroleum products such as crude oil and its derivatives is transporting liquids through commercial pipelines. Liquid transportation through pipelines is considered as one of the major energyconsuming phenomenon in the industry due to turbulence within the fluid. As turbulence increases, it reduces the initial flow rate at which liquids can be pumped. As a remedy to encourage continuous flow of liquid at the prevailing flow rates, a large number of scientists have suggested different passive, active and even interactive techniques to overcome this problem. Recently there have been a growing interest to use the rotating disk in numerous industrial application such as rotating mixing, rotating disk reactor, steam turbines, gas turbines, pumps, and other rotating fluid machines. However, these applications have been considered as energy consuming regimes. In the present work, a high precision rotating disk apparatus (RDA) was designed, fabricated, and used to investigate the turbulent drag reduction characterisation of diesel fuel. The experimental work of this study was divided into three main stages. The first stage was passive drag reduction. In this stage, a number of disks with four riblets types (L, U, RAT and SV- groove) and twelve different dimensions for each type were used. All experiments were performed at rotational disk velocities ranging from 2000 to 3000 rpm, which correspond to a Reynolds number (Re) range of (3.02×105- 4.53×105). The second stage was active drag reduction, which involved using different types of additives with a smooth disk only. A cationic polymer of polyisobutylene (PIB) and two anionic surfactants of sodium di-octyl sulphosuccinate (SDS) and sodium lauryl ether sulphate (SLES) were used as drag reducing agents. These additives were tested individually and as two complex mixtures of PIB-SDS and PIB-SLES. Polymer solutions were prepared in 50, 100, 150, 200, and 300 ppm, while the surfactant solutions were 200, 400, 600, 800, and 1000 ppm. The last stage in this work was the combination of passive and active drag reduction methods by using the same drag reducing agents that were used in the active stage with various structured disks. From the passive results, it was observed that the drag reduction performance increased with decreasing riblets height and it decreased with rotational velocity. The maximum passive drag reduction achieved was 8.048 % for the SV-groove with a riblets height of 900 μm, while it was 0.975 %, 2.683 %, and 6.829 % for the L, RAT, and U-groove, respectively. In contrast, the active results showed a higher drag reduction compared to the passive results. The drag reduction increased with polyisobutylene concentration until a critical value at which the maximum drag reduction was achieved. The same behaviour was also observed for the two types of surfactant and the two complex mixtures. The highest drag reductions for PIB, SDS, and SLES with the smooth disk were 19.197 %, 8.03 %, and 13.8 %, respectively at a polymer concentration of 150 ppm and a surfactant concentration of 1000 ppm. However, the drag reduction percentage (%DR) of the complex mixtures was higher than their individual results, whereby the maximum %DR of PIB-SDS and PIBSLES with the smooth disk was 25.7 % and 25.35 %, respectively. The passive-active interactive results showed the same additive behaviour with all riblets types, whereby the drag reduction increased with additive concentration. However, the maximum drag reduction was achieved with high riblets dimensions (H=3100 μm) with all additive types. Moreover, the drag reduction values of the smooth disk were higher than that of all the structured disks with a height of 900 μm. Overall, a 26.93 % DR was achieved in this study for the complex mixture of PIB (150 ppm) and SLES (1000 ppm) using the SV-groove with a height of 3100 μm. Finally, a computational fluid dynamics simulation using commercial ANSYS, CFX code was employed in order to explain the real mechanism of the riblets drag reduction. The simulation results clearly explained the drag reduction mechanism by the riblets, as well as providing good agreement between the simulation and observed experimental results.